Interactive Design of 3D -Tactile Map for Visual Impairment people - Arif, Muhammad; Ramdani, Fatwa; Budi, Agung Setia (Faculty of Computer Science (FILKOM) Brawijaya University, 2021)
on maps. In general, the map can only be used by users who are can see visually and blind people have difficulty reading the map because there is no map for the visual impairment in 3D. This map has the advantage of being printable so that it is easy to understand and use for blind users. Amid the development of the map, the authors developed a 3D interactive map design that can accommodate the needs of blind users. This development is generated from DSM data through aerial surveys using drones altered to produce a smoother surface so that it can be reconstructed into a 3D design and analysis of the level of texture density and the level of conformity to the real or original shape and reconstruction using aims to improve and model. Shape to fit the 3-dimensional printing process. The voice module is installed using the RFID Tag identification that is embedded in the 3D map and the RFID Reader in the user's hand, with voice data processing. This innovation that has been developed has the advantage of having a 3-dimensional shape that can be felt, texture, shape, and height equipped with braille-shaped markings that are specially made using Riglet for easy reading and sound as a support to improve the blind's people spatial understanding and spatial literacy.